Arts organization papers, - Wilkening, Susan (Mrs. H. F.), 1885-
Minutes, correspondence, and assorted other papers belonging to Susan Wilkening (Mrs. H. F.) and related to the Pacific Northwest Art League and the Spokane Art Board. The collection includes the programs and correspondence of the Pacific Northwest Art League. Also includes the by-laws, constitution, correspondence and board minutes of the Spokane Art Board. These papers would all have been from the earliest days of the organizations when Wilkening was involved.